TOXIC PARENTS DALAM TINJAUAN HUKUM KELUARGA ISLAM - Nurfadhila Yunus; Supardin; Nurfaika Ishak (Universitas Islam Negeri Alauddin Makassar, 2024)
This article attempts to examine toxic parents from the perspective of Islamic family law, covering several aspects, including the impact of toxic parents on children, the existence and implementation of Islamic family law regarding toxic parents. This research is a type of library research with a normative juridical and sharia approach. The findings indicate that the parenting applied by parents who practice incorrect parenting patterns clearly contradicts what is regulated in Islamic family law and/or marriage law, as well as what has been commanded by the Prophet Muhammad (PBUH) in raising and caring for children. Incorrect parenting can have negative impacts on a child's development, as regulated in Law No. 1 of 1974 concerning Marriage, Article 45, paragraph 1, which states that both parents are obliged to care for and educate their children to the best of their ability. The Prophet Muhammad (PBUH) recommended caring for children with love and fulfilling all rights and duties as parents. In this context, the government needs to take firm action in imposing sanctions on parents who engage in physical or verbal abuse in raising children. Additionally, parents should prioritize their obligations and duties in nurturing and educating their children to ensure that all of the children's rights are fulfilled.